2014
DOI: 10.1021/jp508883v
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the PhC≡C/Au Interface

Abstract: The phenylethynyl group (PhCC) has attracted attention recently as a new way to passivate gold surfaces, but little is known of the interfacial structure and bonding. Here we employ density functional theory to investigate the organogold interfaces between PhCC and the flat Au(111) surface as well as between PhCC and a model gold nanocluster (Au 20 ). Although isolated PhCC prefers the three-coordinate hollow site on the perfect Au(111) surface, formation of the PhCCAu adatom CCPh motif becomes energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 46 publications
9
58
0
Order By: Relevance
“…For example, carbon compounds with gold are almost exclusively described in terms of the covalent form structure 1b. Indeed, gold can in some compounds be considered as a replacement atom for carbon or hydrogen, allowing description in terms of standard singly, doubly, and triply bonded structures (23)(24)(25). More generally though, organometallic compounds dominated by covalent bonding are described in terms of ionic structures, allowing for integration of these bonds with standard valence descriptions of the metal.…”
Section: Standard Chemical Bonding Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, carbon compounds with gold are almost exclusively described in terms of the covalent form structure 1b. Indeed, gold can in some compounds be considered as a replacement atom for carbon or hydrogen, allowing description in terms of standard singly, doubly, and triply bonded structures (23)(24)(25). More generally though, organometallic compounds dominated by covalent bonding are described in terms of ionic structures, allowing for integration of these bonds with standard valence descriptions of the metal.…”
Section: Standard Chemical Bonding Scenariosmentioning
confidence: 99%
“…The relevant electrogenativities are Au 2.4, S 2.5, Se 2.4, and Te 2.1, and gold is known to form many stable compounds in its auride form (23,26). Further, covalentbonding notations such as structure 1b are usually applied to goldoxygen bonds (53,54), analogous to that used for gold-carbon bonds (23)(24)(25). Finally, strong van der Waals interactions are known to provide bonding with closed-shell ligands such as disulfides (RSSR), as well as with nitrogen bases like ammines, pyridine, and 1,10-phenanthroline.…”
Section: Bond Polarization Data Indicates That Only Structures 1b Andmentioning
confidence: 99%
“…[2] Alternatively, larger nanoparticles may be etched using excess thiol. [3] Syntheses incorporating an etching step, alternatively described as size focusing or digestive ripening, are recently shown to give high yield of many clusters including Au 18 (SR) 14 ,[4] Au 20 (SR) 16 ,[5] Au 23 (SR) 16 ,[6] Au 24 (SR) 20 ,[5b, 7] Au 25 (SR) 18 ,[8] Au 28 (SR) 20 ,[3a, 9] Au 36 (SR) 24 ,[10] Au 38 (SR) 24 ,[11] Au 40 (SR) 24 ,[12] Au 68 (SR) 34 ,[13] Au 99 (SR) 42 ,[14] Au 144 (SR) 60 ,[15] Au 333 (SR) ∼80 ,[16] and Au ∼500 (SR) ∼120 through tuning of the synthetic conditions. [17] In addition, etching is successful in production of alloys of these clusters, including Au 24 Pd(SR) 18 ,[18] Au 24 Pt(SR) 18 ,[19] and Au 144-x Ag x (SR) 60 .…”
mentioning
confidence: 99%
“…Jiang et al. investigated the interfacial binding of PhC≡C‐ groups on an ideal Au 20 cluster and suggested that the formation of a monomeric or a V‐shaped dimeric staple motif became energetically preferred over the other binding modes . More importantly, Wang et al.…”
Section: Figurementioning
confidence: 99%